Dinamika Kurikulum Mardeka dalam Proses Pembelajaran di Sekolah Dasar Islam Terpadu Ishlahul Ummah - Takwim; Fadriati (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
A curriculum is a prearranged set of educational resources that can be used in conjunction with learning activities. Curriculum is a way to gauge a person's daily capacity to carry out the learning process. The research methodology used in this study is a literature review. A literature review is a type of research project that involves gathering data and information from publications and national journals, along with related references. The study's findings and analysis show that the curriculum has goals, forms, procedures, challenges, and stages intending to enhance students' growth and development in line with academic objectives. One curriculum type that is used in the learning process is the independent curriculum, which is based on my research. The procedures that are followed include trying learning outside of the classroom if it is typically done in one, as well as putting strategies in place to help teachers and students effectively communicate through teaching and learning activities. with a technique for conducting discussions that keeps pupils from experiencing psychological fear. Nonetheless, challenges exist, including inadequate human resources and the immaturity of educational institutions and staff. Because it sheds light on the mechanics of learning using the Independent Learning Curriculum, this research is highly significant.